IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS NILAI ISLAM DI MADRASAH IBTIDAIYAH PLUS BAITUL IZZAH, CIREBON - Azwar Anas (CV. Kalimasada Group, 2026)
This study analyzes the implementation of Islamic-values-based character education at Madrasah Ibtidaiyah Plus Baitul Izzah, a private, C-accredited Islamic elementary school in Setu Kulon Village, Weru District, Cirebon Regency. Using a qualitative single-case-study design, data were collected through in-depth interviews, participant observation, and document analysis, and analyzed with the interactive model of Miles, Huberman, and Saldana. The findings show that the madrasah applies a holistic concept integrating a Qur’an memorization (tahfidz) program with traditional literacy based on the Kitab Kuning and the Pegon script as an effort to preserve the Islamic literacy heritage of the Nusantara. Its main mechanism is structured classical habituation—congregational Duha and Zuhur prayers, communal supplication, salawat, and Qur’an instruction using the Yanbua method—reinforced by teachers’ exemplary conduct (uswah hasanah). The results are evident in memorization achievements, the strengthening of moral-cultural identity through Pegon, and behavioral change among students. Supporting factors include the leadership’s commitment, a spiritually conducive environment, and parental involvement, whereas the challenges include time and facility constraints, the influence of social media, and students’ diverse backgrounds. The study concludes that combining habituation, exemplary conduct, and local wisdom is effective for character formation in rural settings.